Contesting racism: how do the black middle-class use cultural consumption for anti-racism?. Issue 5 (2nd September 2020) - Meghji, Ali
ABSTRACT: Drawing on interviews with thirty-two black British professionals, and ethnographic work in middle-class cultural spaces across London, this paper asks 'How do the black middle-class use cultural consumption for anti-racism?' I argue that the black middle-class contest the racial hierarchy at three levels through their cultural consumption: the material, the ideological, and the symbolic. At the material level, black middle-class people consume cultural forms they decode as 'white' in order to establish an equity with whites in levels of cultural capital. At the ideological level, black middle-class people consume cultural forms that uplift meanings and representations of blackness, thus challenging controlling images of blackness. Lastly, at the symbolic level, black middle-class folks create and sustain cultural spaces where black people's cultural and symbolic knowledge is given proper recognition and authority.